Characterization of a novel HLA‐DRB1*03 allele, DRB1*03:171. (4th March 2020) - González‐Escribano, María Francisca; Balas, Antonio; Muñoz‐García, Raquel; Ortiz‐Aljaro, Pilar; Vicario, José Luis
Abstract : DRB1*03:171 was described in a Caucasian Spanish family.